2021
DOI: 10.4252/wjsc.v13.i7.685
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms involved in selecting and maintaining neuroblastoma cancer stem cell populations, and perspectives for therapeutic targeting

Abstract: Pediatric neuroblastomas (NBs) are heterogeneous, aggressive, therapy-resistant embryonal tumours that originate from cells of neural crest (NC) origin and in particular neuroblasts committed to the sympathoadrenal progenitor cell lineage. Therapeutic resistance, post-therapeutic relapse and subsequent metastatic NB progression are driven primarily by cancer stem cell (CSC)-like subpopulations, which through their self-renewing capacity, intermittent and slow cell cycles, drug-resistant and reversibly adaptive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 471 publications
(589 reference statements)
0
4
0
Order By: Relevance
“…Despite advances in the selection of CSCs in NB, targeting these cells effectively remains challenging ( 53 ). Our study examined the activity of signaling pathways associated with mRNAsi-related genes, and identified several drugs targeted at certain pathways that suggested better efficacy in the high-risk score group.…”
Section: Discussionmentioning
confidence: 99%
“…Despite advances in the selection of CSCs in NB, targeting these cells effectively remains challenging ( 53 ). Our study examined the activity of signaling pathways associated with mRNAsi-related genes, and identified several drugs targeted at certain pathways that suggested better efficacy in the high-risk score group.…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation for this effect could be that the low growth rate lends more time for these cells to repair chemotherapy damage [106,107]. However, another phenomenon could contribute to this stage, such as higher expression of ABC drug transporters in these cells [108,109]. On the other hand, the effect that we attribute to the increase in slowly dividing cells could be due to other effects, such as the inhibition of angiogenesis, widely attributed and recently countersigned for the PEDF protein [110].…”
Section: Discussionmentioning
confidence: 99%
“…For example, neuroblastoma-derived mesenchymal stem cells have been found to play a pro-tumoral role in the TME, promoting immune evasion and the invasion and metastasis of tumor cells [ 96 ]. The number of molecular elements identified as being linked mechanistically to stemness is also increasing [ 96 , 97 , 98 ]. Several signaling pathways, such as the PI3K/Akt/mammalian target of rapamycin (mTOR; PAM), Wnt, and RAS/RAF/MEK/ERK pathways, as well as dysregulated p53 signaling, are known to promote and maintain stemness in neuroblastoma.…”
Section: Long Non-coding Rnas In Neuroblastomamentioning
confidence: 99%
“…VEGF has been identified as a factor that stimulates the survival, angiogenesis, and etoposide chemoresistance of neuroblastoma cells; recent studies conducted with murine xenograft models, however, have indicated that VEGF expression is not correlated with angiogenesis, but rather with the neural differentiation of neuroblastoma cells [ 119 , 120 , 121 , 122 ]. MALAT1 also contributes to the maintenance of stemness, promoting immune evasion, migration, invasion, and metastasis [ 98 ]. These effects are mediated via the PAM pathway, the RAS/RAF/MEK/ERK pathway, and the tyrosine kinase receptor Axl.…”
Section: Long Non-coding Rnas In Neuroblastomamentioning
confidence: 99%
See 1 more Smart Citation